Interaksi Antara Lingkungan Kerja, Karakteristik Pribadi terhadap Stres Kerja: Efek Moderasi Kemampuan Adaptasi pada Karyawan Pada PT Sari Madu - Honkley, Tony (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2024)
Employee work-related stress can adversely impact their psychological and physical well-being, as well as diminish the overall productivity of the firm. The work environment and individual traits of individuals are seen as catalysts for occupational stress, particularly when employee flexibility is deficient. Consequently, it is essential for firms to evaluate these aspects to develop suitable strategies for addressing work-related stress issues. The research included 110 employees as participants. The analytical approach employed is the Structured Equation Model (SEM) utilizing Partial Least Squares (PLS), which is proficient for small sample sizes and intricate models. The study's results demonstrate that every aspect related to the work environment, individual traits, and adaptability positively and significantly influences job-related stress. Moreover, flexibility serves as a moderator that might enhance the correlation between the work environment and individual traits in affecting employee job stress levels.